2014
DOI: 10.3177/jnsv.60.122
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Reduces the Hypoxia-Induced Resistance to Doxorubicin in Breast Cancer Cells

Abstract: Summary Resveratrol (3,4′,5-trihydroxy-trans-stilbene) is known to enhance the cytotoxicity of the anticancer drug doxorubicin. On the other hand, breast cancer MCF-7 cells acquire resistance to doxorubicin under hypoxic conditions. In this study, we investigated the effect of resveratrol on hypoxia-induced resistance to doxorubicin in MCF-7 cells. Resveratrol and its derivative 3,5-dihydroxy-4′-methoxy-trans-stilbene, but not 3,5-dimethoxy-4′-hydroxy-trans-stilbene, cancelled hypoxia-induced resistance to dox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Although, there is no direct evidence for increased CBR1 expression from the ingestion of polyphenols (with the exception of stilbenes (Mitani et al, 2014)), their induction effect on CBR1 is highly probable. From this point of view, induction of CBR1 by polyphenols could represent the way of improving chemoprotection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although, there is no direct evidence for increased CBR1 expression from the ingestion of polyphenols (with the exception of stilbenes (Mitani et al, 2014)), their induction effect on CBR1 is highly probable. From this point of view, induction of CBR1 by polyphenols could represent the way of improving chemoprotection.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the ability of stilbenes with 3,5-dihydroxy groups to decrease CBR1 expression in MCF-7 cells by decreasing HIF-1a protein expression was reported (Mitani et al, 2014). Many flavonoids have also been reported to suppress HIF-1a expression and hence down-regulate hypoxia-inducible genes, however, the connection between the effect of flavonoids on HIF-1a and CBR1 has never been assessed directly.…”
Section: The Regulation Of Cbr1 Transcript By Polyphenolsmentioning
confidence: 98%
“…As mentioned above, some researches argued that transcriptional activation of CBR1 is regulated through a transcription factor hypoxia-inducible factor-1α. 18,19,29) Further accumulation of precise information about the factors responsible for the transcriptional regulation of CBR1 and sequence of the promotor region is therefore required to explain the clear discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that CBR1 is highly induced during the development of DOX resistance through formation of ROS, as well as previously reported hypoxia. 18,19) Based on results of our previous promotor gene analysis 30) and the marked induction during the treatment of LoVo cells with the Nrf2 activator SFN (Fig. 4A), we assume that up-regulation of CBR1 is mainly mediated due to activation of Nrf2/Kelch-like ECH-associated protein-1 (Keap1) signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation